Pendampingan Pembuatan Video Stop Motion untuk Pemasaran Produk UMKM di Patuk Gunungkidul - Asih Pujiastuti; Astika Ayuningtyas; Harliyus Agustian (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2020)
By developing the commercialization of micro, small and medium enterprise (MSME) products in Patuk Gunungkidul district, Instagram social media can be used by creating content in the form of stop motion videos. The creation of stop-motion videos requires the knowledge and skills of MSME actors. Help with the production of stop motion videos is therefore necessary to improve the marketing of products. The assistance consists of introducing stop-motion video, photo-taking techniques and posting stop-motion video content on Instagram. The results of mentoring activities revealed that SMEs in Patuk Gunungkidul's sub-district had the skills to create stop-motion videos on their products. In addition, they were also able to post videos of products they had made on Instagram social networks.